Diversity of Indigenous Bacteria from Mangrove Sediments in the Waters of Ambon Bay, Maluku - Tuasalamony, Mutia Musdalifah; Widiyanto, Tri; Rusmana, Iman (Bogor Agricultural University, Indonesia, 2025)
This study aimed to analyze the diversity of indigenous bacteria by comparing culture and non-culture methods and to analyze the physicochemical effects on bacterial diversity in polluted and natural mangrove sediments. The environmental parameter values of mangrove sediments for bacterial growth can change owing to differences in adaptation and tolerance to fluctuations in physicochemical conditions. The number of colonies in natural and polluted areas using the culture method was 6.2 × 104 CFU/g and 5.5 × 104 CFU/g, respectively. A total of 33 isolates were identified, with 17 and 16 isolates from the natural and polluted areas, respectively. The most common isolates found in both areas were Acinetobacter haemolyticus strain FBC636 and Exiguobacterium acetylicum strain IAE17. Using the nanopore sequencing method, the total number of colonies in the natural and polluted areas was 69,761 and 58,412 colonies, respectively. A total of 12,954 bacterial species were identified, with 6,837 species in the natural area and 6,117 in the polluted area. The most common isolate found was Sulfurovum aggregans. Physicochemical conditions influenced the differences in bacterial diversity between the natural and polluted areas in the mangrove areas of Ambon Bay.